The association between retinal microvasculature derived from optical coherence tomography angiography and systemic factors in type 2 diabetics - Li, Yi; Wu, Kunfang; Chen, Zilin; Xu, Guihua; Wang, Dingding; Wang, Juanjuan; Bulloch, Gabriella; Borchert, Grace; Fan, Huiya (Frontiers in Medicine, 2023)
Aims: To investigate the correlation between the retinal microvasculature using optical coherence tomography angiography (OCTA) and systemic factors in type 2 diabetes mellitus (T2DM) patients. Methods: This cross-sectional study obtained OCTA data from patients with T2DM administered at Hospital and referred to ophthalmic services. Patient data about demographics, comorbid conditions, and blood biomarkers were extracted from electronic medical records. Data from OCTA scans obtained by CIRRUS HD-OCT Model 5000 were obtained. Vessel density (VD) and perfusion density (PD) within the superficial capillary plexus, and foveal avascular zone (FAZ) area were automatically segmented. These parameters were tested for their correlations with systemic factors by univariate and multivariable linear regression analyses. Results: A total of 144 T2DM patients (236 eyes) were available for analysis, with mean age of 53.6 (SD=10.34) and 56.9% were male. Chronic kidney disease, cardiovascular disease, increased serum creatinine (Scr), red blood cell count (RBC), platelets (PLT), apolipoprotein B (APOB), and decreased urine albumin to creatinine ratio (UACR) were significantly associated with lower VD and PD (all P<0.013). UACR and triglyceride (TRIG) were significantly correlated with FAZ area (all P<0.017). In multivariate analyses, PLT, eGFR, and APOB were independent risk factors for retinal rarefaction, and UACR was a significant predictor of FAZ area. Conclusion: We found several systemic risk factors, such as PLT, renal function, and lipid profiles were associated with PD, VD, and FAZ area among Chinese T2DM patients.